Модернізація бюджетного планування і прогнозування в контексті гарантування бюджетної безпеки України - Колісник, Олег; Colisnyk, Oleh (ТНЕУ, 2007)
З позиції бюджетної безпеки розглянуто сучасний стан прогнозно-планової роботи в бюджетному процесі. Запропоновано шляхи модернізації бюджетного планування і прогнозування з метою гарантування безпечного розвитку держави. From position of budgetary safety the modern tendencies of the prognosis-planned work in a budgetary process are considered. The ways of modernization of budgetary planning and prognostication with the purpose of guaranteeing of the states safe development are offered.
Modernization of the system of budget planning and prognostication in the context of guaranteeing of budget safety of Ukraine